PUBLIC RELATIONS STRATEGY OF PT. QUALITAS FLAGSHIP 'Q-GOLF' IN INCREASING CUSTOMERS - Muslim Muslim (UNIVERSITAS PAKUAN, 2022)
One way that companies can do to convey the value of their products is by using public relations or public relations. PT Qualitas Andalan Bersama (Q-golf) is a company that provides online golf course booking services through applications on smartphones. The number of Q-golf customers has decreased on 2018-2019. From these data, it can be concluded that the trend of existing customers has decreased which resulted in a decrease in the number of customers. Existing customers do not show loyalty to Q-golf. Q-golf has implemented a public relations strategy to be able to publicize their products with the aim of increasing customer loyalty. However, the results of the PR strategy carried out by Q-golf showed unsatisfactory results. Therefore, the public relations strategy carried out by Q-golf becomes interesting to analyze. The purpose of this study was to determine the PR strategy of PT Qualitas Andalan Bersama in increasing customer loyalty. This study uses a descriptive qualitative approach. The research was conducted by conducting interviews with five informants. The results of this study are the main roles of Q-golf's public relations are press relations, product publicity, and public affairs. Q-golf's public relations role as lobbying and development does not become the main role but is still carried out by Q-golf's public relations. There are seven public relations tools used by the public relations department of Q-golf, namely news, special events, written materials, audio-visual materials, corporate identity materials, public service activities, and websites and social media. The strategies that have been implemented by Q-golf's PR are strategy of publicity, strategy of persuasion, and strategy of image. Public Relations Q-golf does not implement a strategy of augmentation.